2020
DOI: 10.1039/d0qo00339e
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine tetrafluoro-λ6-sulfanyl chlorides: spontaneous addition to alkynes and alkenes in the presence or absence of photo-irradiation

Abstract: A radical addition reaction of Py-SF4Cl to alkynes and alkenes provide pyridine-SF4-alkenes and pyridine-SF4-alkanes under blue LED light irradiation or absence of light irradiation in CPME or without solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…This procedure is an excellent alternative to BEt 3 ‐catalyzed processes, as the borane is often the source of undesired side reactivity or substrate decomposition. In agreement with previous reports, the authors proposed a radical process to explain the reactivity observed [53] …”
Section: Fluorination Levelsupporting
confidence: 91%
See 1 more Smart Citation
“…This procedure is an excellent alternative to BEt 3 ‐catalyzed processes, as the borane is often the source of undesired side reactivity or substrate decomposition. In agreement with previous reports, the authors proposed a radical process to explain the reactivity observed [53] …”
Section: Fluorination Levelsupporting
confidence: 91%
“…In agreement with previous reports, the authors proposed a radical process to explain the reactivity observed. [53]…”
Section: Fluorination Levelmentioning
confidence: 99%
“…Scheme 20 Synthesis pf pyridine-SF4-λ 6 -sulfanyl-alkenes and -alkanes. 23 Key: CPME = cyclopentyl methyl ether A safe, practical and scalable synthesis of SF5Cl in n-hexane under gas-reagent-free conditions was reported by Qing et al (Scheme 21), 24a who optimized the method previously described by Togni et al 24b The reaction of sulphur powder, dry KF and TCICA in the dark, affords SF5Cl along with SO2F2 and SOF2 as by-products. SF5Cl can be easily purified by extraction in n-hexane and the resulting solution can be stored for months without noticeable decomposition.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Scheme 20 Synthesis of pyridine-SF 4 - 6 -sulfanylalkenes and -alkanes. 23 CPME: Cyclopentyl methyl ether.…”
Section: Scheme 23 Synthesis Of Sf 5 -Indoles 26mentioning
confidence: 99%
See 1 more Smart Citation